Alucinar, brincar e escrever: por uma simbolização do gesto - Parente Júnior, Paulo Alves (2025)
Humans need to rely on symbols. However, the symbolization that makes it possible to mediate the world of language and the world of sensory-perceptive reactions is not only about achieving the diacritical connection between signs and logic. There are imaginative, dreampoetic, playful and even symptomatic formulations of experience that can also mediate language with the sensitive body, but that exist precisely to reach affects, emotions and feelings that words cannot reach. A fundamental hypothesis is that the very foundation of language in its full symbolic manifestation needs to be brought together with the multiple forms of feeling and expressiveness. This thesis deals with the way in which the problem of symbolizing gestures is presented in the psychoanalytic tradition that begins with Freud, Ferenczi and Winnicott and in the dialogue with thinkers of post-Kantian philosophy and theories of language. After presenting a broad conception of symbol appropriate to emotional life and differentiating the concept of psychoanalytic symbol from linguistic sign, the gesture will be collected in three key moments of Freud's work: the Project, Fort-da and Moses and Monotheism. It is verified that it passes from the field of specific action of the other to constitute an intimate trace rediscovered in the child's body through hallucination and play, here thought of in forms of rhythm and introjection, which will later also be at play in writing. Language promotes the translation of the gesture into a new abstract spirituality, but this work finds its psycho-historical truth surviving in the debris of the sensitive.